Out of sight, out of mind? The inclusion and identification of people with intellectual disability in public health research. (July 2015) - Brooker, Katie; van Dooren, Kate; Tseng, Chih-Han; McPherson, Lyn; Lennox, Nick; Ware, Robert
Aims: Adults with intellectual disability experience substantial health inequities. Public health research aiming to improve the lives of this population group is needed. We sought to investigate the extent to which a sample of international public health research includes and identifies people with intellectual disability. Methods: In this systematic review, we examined a select number of public health journals to determine (1) how often people with intellectual disability are explicitly included in randomised controlled trials (RCTs) and cohort studies and (2) how the presence of intellectual disability is identified and reported. Results: Among eligible articles in these selected public health journals, it was found that cohort studies passively exclude people with intellectual disability, while RCTs actively exclude this population. Most general population articles that explicitly identified people with intellectual disability did so through self-report or proxy report and databases. Conclusions: A more extensive and adequate evidence base relating to the health of this overlooked population group is needed. A useful first step would be for researchers specialising in intellectual disability to identify how we can best assist mainstream researchers to include and identify people with intellectual disability in their population-level studies.